EFEKTIVITAS PELAKSANAAN EKSTENSIFIKASI WAJIB PAJAK MELALUI KEGIATAN CANVASSING, SOSIALISASI, DAN SURAT HIMBAUAN DALAM RANGKA MENINGKATKAN JUMLAH WAJIB PAJAK (Studi pada Kantor Pelayanan Pajak Pratama Malang Utara) - Hayuningtyas, Refi Cintya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of this research is to know the effectiveness of taxpayers extension activityconducted at the Tax Office of North Malang. It involves canvassing, socialization, and advice letter directed to registered Taxpayers which were analyzed through the total of Taxpayer Identification Number (TIN) registration carried out out after the extension activity. Afterwards analyzing the three extension activities, the most dominant activity that increase the number of registered Taxpayers is determined. The method used in this research is quantitative method with classic assumption test and multiple linear regression models with the least square method. The secondary data, being used in this research, is in time series form from January 2014 to December 2015. The result and the discussions show that activities of canvassing, socializing, and advise letter affect the number of registered Tax Payer. Therefore, improving the three activities can increase the number of registered taxpayers significantly. The multiple regresion analysis conducted by the researcher found that at the t test canvassing activity had the biggest t value count and beta coefficient among other activities. The most dominant extension activity that effectively give contribution towards the increase of registered tax payers at Tax Office of North Malang is determined. The result of this research can be used as the basis of policy improvements related to the effort of increasing the number of registered taxpayers.Keywords: Tax Payers Extension, canvassing, socialization, advice letter, Tax Office